(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Physical fitness, particularly cardiorespiratory endurance (VO₂max), is an essential component supporting athlete performance in combat sports such as Wushu. Adequate aerobic capacity enables athletes to maintain movement intensity, technical performance, and recovery efficiency during training and competition. However, the aerobic fitness profile of regional-level wushu athletes remains insufficiently documented, especially in club-based athlete development programs. Therefore, this study aimed to evaluate the physical fitness condition, specifically VO₂max levels, of Gresik Wushu Club athletes using the Cooper Test (12-minute run). This study employed a descriptive quantitative method with a cross-sectional design. The participants consisted of 10 wushu athletes aged between 13 and 20 years. Data collection was conducted through the Cooper Test by measuring the total distance covered within 12 minutes. The estimated VO₂max values were subsequently calculated using the Cooper formula and classified according to fitness level categories. The findings revealed that the average running distance achieved by the athletes was approximately 2051.55 meters, with an average VO₂max value of 34.57 ml/kg/minute. Most athletes demonstrated moderate to low physical fitness levels, with VO₂max values below 35 ml/kg/minute indicating insufficient aerobic endurance capacity. Only a small proportion of athletes achieved the good fitness category, while several athletes remained in poor and very poor categories. In conclusion, the cardiovascular endurance level of Gresik Wushu Club athletes generally still requires improvement. Therefore, more structured, systematic, and sustainable aerobic training programs are needed to increase VO₂max capacity and support optimal athletic performance during training and competition.